Characterization of complete mitochondrial genome in Myuroclada maximowiczii (G.G. Borshch.) Steere & W.B. Schofield. Issue 7 (3rd July 2021) - Han, Yeong-Deok; Jung, Jin-Woo; Choi, Youngeun; Yoon, Kwang-Bae; Yoon, Young-Jun
Abstract: The mitogenome of Myuroclada maximowiczii (GenBank accession number MT834960) has a total length of 104, 216 bp and encodes 40 protein-coding genes, three ribosomal RNAs, and 24 transfer RNAs. The overall nucleotide composition is asymmetric (29.6% A, 29.4% T, 21.2% G, and 19.8% C), with AT content (59.0%) higher than GC content (41.0%). The gene arrangement of this mitogenome is identical to that in other bryophytes. Phylogenetic trees were constructed using complete mitochondrial genome sequences of 24 bryophytes publicly available in GenBank and the mitogenome sequence derived in this study. Our phylogenetic analysis revealed that M. maximowiczii clustered in a clade with other hypnalean taxas.